Total Kapang Khamir dan Identifikasi Bakteri Patogen pada Sediaan Jamu Tradisional - Anggraeni Sih Prabandari (Indonesian Journal on Medical Science, 2023)
Traditional herbal medicine has had risk of yeast/mold and bacteria contamination due to its raw material and process of production. BPOM RI had regulated microbiological quality standard of traditional herbal medicine. UMKM X in Surakarta had produced four variants of traditional herbal medicine, marketed at Surakarta and around. The aim of this study was to determine the number of yeast/mold contamination, identification yeast contaminant and pathogenic bacteria include Escherichia coli and Staphylococcus aureus. It was descriptive research cross sectional design. Beras kencur, kunyit asam, jahe rempah and temulawak were taken randomly to determine the number of yeast/ mold and identification of yeast. Escherichia coli and Staphylococcus aureus was identified by their growth characteristic on selective diferential medium agar. The result showed all samples had high number of yeast/mold, more than 103 colony/ml. We identified two species of yeast, they are Aspergillus flavus and Aspergillus niger. Escherichia coli was identyfied from all of the samples, but only 80% had Staphylococcus aureus contamination. We concluded all of the samples were not meet BPOM RI regulation.